The impact of the conceptual strategy on the attainment and cultural awareness of the students of the second-grade average in the subject of sociology - Wissam Aziz Obaid AlHamzawy (Genius Journals, 2024)
The current research aims at identifying the impact of the strategy of conceptual understanding on the attainment and cultural awareness of the students of the second-grade medium in the subject of sociology. To this end, two hypotheses have been drafted: There is no statistically significant difference at the level of (0.05) between the middle grades of the students of the experimental group taught by adopting the strategy of enclosing concepts and the students of the control group who studied the subject itself by adopting the usual method of achieving the subject.
Keywords: Concept briefing strategy; educational achievement; cultural awareness